Effect of epiretinal electrical stimulation on the glial cells in a rabbit retinal eyecup model - Henze, Dean; Majdi, Joseph A.; Cohen, Ethan D. (Frontiers in Neuroscience, 2024)
Introduction We examined how pulse train electrical stimulation of the inner surface of the rabbit retina effected the resident glial cells. We used a rabbit retinal eyecup preparation model, transparent stimulus electrodes, and optical coherence tomography (OCT). The endfeet of Müller glia processes line the inner limiting membrane (ILM). Methods To examine how epiretinal electrode stimulation affected the Müller glia, we labeled them post stimulation using antibodies against soluble glutamine synthetase (GS). After 5 min 50 Hz pulse train stimulation 30 μm from the surface, the retina was fixed, immunostained for Müller glia, and examined using confocal microscopic reconstruction. Stimulus pulse charge densities between 133–749 μC/cm2/ph were examined. Results High charge density stimulation (442–749 μC/cm2/ph) caused significant losses in the GS immunofluorescence of the Müller glia endfeet under the electrode. This loss of immunofluorescence was correlated with stimuli causing ILM detachment when measured using OCT. Müller cells show potassium conductances at rest that are blocked by barium ions. Using 30 msec 20 μA stimulus current pulses across the eyecup, the change in transretinal resistance was examined by adding barium to the Ringer. Barium caused little change in the transretinal resistance, suggesting under low charge density stimulus pulse conditions, the Müller cell radial conductance pathway for these stimulus currents was small. To examine how epiretinal electrode stimulation affected the microglia, we used lectin staining 0–4 h post stimulation. After stimulation at high charge densities 749 μC/cm2/ph, the microglia under the electrode appeared rounded, while the local microglia outside the electrode responded to the stimulated retina by process orientation inwards in a ring by 30 min post stimulation. Discussion Our study of glial cells in a rabbit eyecup model using transparent electrode imaging suggests that epiretinal electrical stimulation at high pulse charge densities, can injure the Müller and microglia cells lining the inner retinal surface in addition to ganglion cells.